2019
DOI: 10.4330/wjc.v11.i10.221
|View full text |Cite
|
Sign up to set email alerts
|

Cellular models for human cardiomyopathy: What is the best option?

Abstract: The genetic cardiomyopathies are a group of disorders related by abnormal myocardial structure and function. Although individually rare, these diseases collectively represent a significant health burden since they usually develop early in life and are a major cause of morbidity and mortality amongst affected children. The heterogeneity and rarity of these disorders requires the use of an appropriate model system in order to characterize the mechanism of disease and develop useful therapeutics since standard dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 130 publications
0
13
0
Order By: Relevance
“…There is thus a need for models that can recapitulate key features observed in human cardiomyopathies and can be used for disease modeling and therapeutic testing. Animal models are the most common models for cardiomyopathies [ 13 ] but have inherent limitations to recapitulate complex human physiopathology as well as inter-patient genetic variability [ 14 , 15 ]. For these reasons, the translation of targeted therapies for cardiomyopathies from animal trials to human subjects has been limited so far.…”
Section: Introductionmentioning
confidence: 99%
“…There is thus a need for models that can recapitulate key features observed in human cardiomyopathies and can be used for disease modeling and therapeutic testing. Animal models are the most common models for cardiomyopathies [ 13 ] but have inherent limitations to recapitulate complex human physiopathology as well as inter-patient genetic variability [ 14 , 15 ]. For these reasons, the translation of targeted therapies for cardiomyopathies from animal trials to human subjects has been limited so far.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, iPSCs offer unprecedented opportunities since these cells can be directed to become any cell type in the body [ 15 ]. iPSC-derived cardiomyocytes (iPSC-CMs) represent a good cellular model in which disease mechanisms can be experimentally deciphered in a human context [ 16 ]. A significant number of PA patients develop cardiac complications, and available evidence suggests that this cardiac dysfunction is mainly driven by the accumulation of toxic metabolites [ 2 , 3 , 17 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Taken together, the previous reports provide substantial information on how to model several outcomes that account for the cardiac deterioration observed in many COVID-19 patients. Studies that use patient-derived hiPSC-CMs carrying inherited diseases can also be found in the literature ( Granéli et al, 2019 ; Hoes et al, 2019 ; Jimenez-Tellez and Greenway, 2019 ). Several of these models can be adopted to evaluate additive effects of COVID-19 and pre-existing comorbidities such as heart failure, cardiomyopathies, diabetes.…”
Section: Modeling the “Covid-19 Cardiomyocyte” In Vitromentioning
confidence: 99%